The Host Response to Viral Infections Reveals Common and Virus-Specific Signatures in the Peripheral Blood - Tsalik, Ephraim L.; Fiorino, Cassandra; Aqeel, Ammara; Liu, Yiling; Henao, Ricardo; Ko, Emily R.; Burke, Thomas W.; Reller, Megan E.; Bodinayake, Champica K.; Nagahawatte, Ajith; Arachchi, Wasantha K.; Devasiri, Vasantha; et al. (Frontiers in Immunology, 2021)
Viruses cause a wide spectrum of clinical disease, the majority being acute respiratory infec-tions (ARI). In most cases, ARI symptoms are similar for different viruses although severity can be variable. The objective of this study was to understand the shared and unique elements of the host transcriptional response to different viral pathogens. We identified 162 subjects in the US and Sri Lanka with infections due to influenza, enterovirus/rhinovirus, human metap-neumovirus, dengue virus, cytomegalovirus, Epstein Barr Virus, or adenovirus. Our dataset allowed us to identify common pathways at the molecular level as well as virus-specific dif-ferences in the host immune response. Conserved elements of the host response to these viral infections highlighted the importance of interferon pathway activation. However, the magni-tude of the responses varied between pathogens. We also identified virus-specific responses to influenza, enterovirus/rhinovirus, and dengue infections. Influenza-specific differentially ex-pressed genes (DEG) revealed up-regulation of pathways related to viral defense and down-regulation of pathways related to T cell and neutrophil responses. Functional analysis of en-tero/rhinovirus-specific DEGs revealed up-regulation of pathways for neutrophil activation, negative regulation of immune response, and p38MAPK cascade and down-regulation of vi-rus defenses and complement activation. Functional analysis of dengue-specific up-regulated DEGs showed enrichment of pathways for DNA replication and cell division whereas down-regulated DEGs were mainly associated with erythrocyte and myeloid cell homeostasis, reac-tive oxygen and peroxide metabolic processes. In conclusion, our study will contribute to a better understanding of molecular mechanisms to viral infections in humans and the identifica-tion of biomarkers to distinguish different types of viral infections.